La fractura mexicana y el golpe de 1954 en Guatemala - Loaeza, Soledad (El Colegio de México, A.C., 2016)
This article reconstructs Mexican politics in the period leading up to the crisis that ended with the U.S.-backed coup against Guatemalan President Jacobo Arbenz in June 1954, questioning the two general assumptions that guide academic research into Mexican foreign policy in the second half of the 20th Century: first, that foreign policy is a source of national consensus; and second, that there is a special relationship between the United States and Mexico in which the two countries agree to disagree in questions of international politics to the extent that their respective strategic interests are not at stake.         The Guatemalan crisis disproves both assumptions. Firstly, it ended the divide between Cardenism and anti-Cardenism that had been the axis around which Mexico’s political contradictions had revolved since the 1930s; and secondly, during the final moments of the Guatemalan crisis, President Ruiz Cortines cooperated with Washington in the struggle to eliminate communist influence from the hemisphere and adopted the measures that had been requested of him. The understood values between Mexico and the United States did not intervene in this case, in other words. This episode makes clear the ideological alliance between the two countries and sets the stage for the mobilizations in solidarity with the Cuban Revolution.